2021
DOI: 10.1111/cea.13962
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and mycobiome interaction in house dust mites and impact on airway cells

Abstract: Background Major allergen sources Dermatophagoides farinae, Dermatophagoides pteronyssinus and Tyrophagus putrescentiae have been reported to have distinct microbiomes. The purpose of this study was to investigate the effect of each mite on airway epithelial cells as a model of airway allergic disease. Methods Transcriptomic analysis (RNA‐seq) of an airway epithelial cell line (BEAS‐2B) was performed to compare gene expression patterns after treatment with extracts of three mite species (D. farinae, D. pterony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Furthermore, in our previous microbiome study of D. farinae and Tyrophagus putrescentiae , both mites contained Gram-negative bacteria, such as Bartonella , and bacteria-derived LPS [ 8 ]. We also showed that D. farinae possessed greater bacterial concentration and LPS than D. pteronyssinus and that the immune response pathway against bacteria was activated only in D. farinae -treated human airway cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our previous microbiome study of D. farinae and Tyrophagus putrescentiae , both mites contained Gram-negative bacteria, such as Bartonella , and bacteria-derived LPS [ 8 ]. We also showed that D. farinae possessed greater bacterial concentration and LPS than D. pteronyssinus and that the immune response pathway against bacteria was activated only in D. farinae -treated human airway cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…BEAS-2B cells were maintained in Dulbecco's Modified Eagle Medium/F40 medium supplemented with 10% inactivated fetal bovine serum at 37°C and 5% carbon dioxide. HDM was used to treat cells seeded at a concentration of 1 × 10 6 cells/well in six well plates [ 20 ]. Cells were sampled 24 hr after a single exposure to 100 μ g/mL each of the ampicillin treated- D. farinae and untreated D. farinae extracts.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, LPS inhibitor treatment reduces the amount of IL-6 and IL-8 released from BEAS-2B cells after treatment with house dust mite extract. This indicates that bacterial components, such as endotoxins, act synergistically on airway epithelial cells to induce an inflammatory response [ 23 ]. Similar to these findings, reduced endotoxin levels in GCE owing to antibiotic usage are likely associated with a decrease in allergic airway inflammation in bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to insects ( Chakraborty et al., 2020 ; Višňovská et al., 2020 ; Kim et al., 2021a ; Guo et al., 2022 ), the research on associations between fungi and ticks is limited. The majority of the available studies are focused on entomopathogenic fungi, mainly of the Beauveria and Metarhizium genera, and their prospective use in the biological control of ticks ( Kalsbeek et al., 1995 ; Mitina et al., 2011 ; Munteanu et al., 2014 ; Wassermann et al., 2016 ).…”
Section: Pathogensmentioning
confidence: 99%
“… Kim et al. (2021a) discovered that nymphs of I. scapularis infected with B. burgdorferi s. l. secreted significantly more saliva proteins while suppressing antimicrobial peptides up to 85-fold compared to uninfected ticks.…”
Section: Microbiome In Tick Organsmentioning
confidence: 99%